Advancements in regulatory agility, regional collaboration, and digital transformation: insights from the Asia Partnership Conference of Pharmaceutical Associations (APAC) - Sannie Siaw Foong Chong; Stephanie Hui Min Ong; Siew Mei Long; Masaaki Kanno; Usanee Harnpramukkul; Kum Cheun Wong; Asawari Sathaye; Mamta Singh; Manish Paliwal; Huyen Do; Helene Sou; Richard Simon R. Binos (AAPS Open)
Abstract Purpose The Asia Partnership Conference of Pharmaceutical Associations (APAC) examines recent developments in regulatory practices across Asia, focusing on regulatory agility, regional collaboration, and digital transformation. The paper identifies key improvements made by national regulatory authorities (NRAs) in adopting regulatory agilities over a two-year span. It also suggests optimizing regional reliance pathways and recommends best practices for implementing e-submission, real-world evidence (RWE), decentralized clinical trials (DCTs), and paperless e-labelling. Methods APAC surveyed all 14 member associations to track progress in regulatory agility implemented by our NRAs from 2022 through April 2024. Additionally, APAC assessed the uptake of regional reliance pathways and the implementation levels of e-submission, RWE, DCTs, and paperless e-labelling. Through the analysis of case studies and survey results, the paper aims to identify key trends, challenges, and opportunities in the regulatory landscape. Results Nine of twelve NRAs have advanced in regulatory agility, with Thai FDA leading with a 36% improvement and ranking 7th in the number of best practices implemented. e-Labeling adoption rose by 50%, and there was a 17% increase in the use of multiple sites under one license, good reliance practices, and acceptance of electronic Certificates of Pharmaceutical Product (eCPP) and Good Manufacturing Practice (eGMP). Perceived issues with the ASEAN Joint Assessment (JA) procedure include timeline constraints, limited flexibility in choosing participating NRAs, and country-specific requirements. NRAs have achieved 100% adoption of e-submissions and 50% for paperless e-labeling. Additionally, 67% accept data from DCTs and RWE using good reliance practices. However, 42% still require paper documents in e-submissions, and 50% continue to accept dossier format different from the International Council for Harmonisation Electronic Common Technical Document (ICH CTD). Conclusions APAC supports adopting agility best practices to reduce country-specific requirements, optimizing the ASEAN JA procedure. APAC also values strategic partnerships with NRAs, as demonstrated by the case studies of Vietnam and India. The shift towards digital transformation is evident, with 50% adoption of paperless e-labeling and 100% adoption of e-submissions, though not all processes are paperless with the use of ICH CTD dossier format. Overall, continued alignment with international standards for implementing eCTD, RWE, and DCTs is required in all 12 economies to realize the full benefits of globally harmonized digital advancement.